Evaluation of cytotoxicity and Apoptotic effects of Simarouba glauca on the Prostate Cancer Cell Lines PC3 - Omar Sadik Shalal; Sajjad Mohsin Irayyif (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the anti-proliferative and pro-apoptotic activities of simarouba glauca on prostate cancer cell lines PC-3. Method: This cross-sectional study was conducted at Iraqi centre for Genetic and Cancer Research from 15th January to 20th June 2021. The evaluation was designed through apoptotic and membrane depolarisation assays. Methanol extract at 0.29ug/ml, 29ug/ml and 290ug/ml doses were used, while rifampicin acted as the positive control and dimethyl sulfoxide acted as the negative control. Real time gene expression was also done to evaluate the levels of messenger ribonucleic acid expression. Data was analysed using SPSS 16. Results: The methanol extract inhibited 50% of the PC-3 cells at a mean concentration of 35.24±0.23ug/mL compared to 15.31±1.83ug/mL for positive control. The extracts pushed PC3 cells significantly into early apoptosis compared to the positive control (p<0.05). The extracts greatly boosted the percentage of mitochondrial membrane potential depolarisation. Methanol extract was found to under-express both vascular endothelial growth factor A by 5-fold and arachidonate 5-lipoxygenase by 4-fold compared to positive control (p<0.05). Conclusion: Simarouba glauca methanol extracts were found to differentially control proliferation and apoptosis in cancer cell lines PC-3. Keywords: Methanol, Plant extracts, Gene expression, Prostatic neoplasms, Phytochemicals, Drug design.